2023
DOI: 10.3389/fendo.2022.990442
|View full text |Cite
|
Sign up to set email alerts
|

Muscle plays a more superior role than fat in bone homeostasis: A cross-sectional study of old Asian people

Abstract: ObjectivesThe aim of this study was to discover the role of fat and muscle in bone structures, as well as the relationship between obesity and sarcopenia on age-related osteoporosis.MethodsA total of 400 participants (65.0 ± 8.2 years old, 42.3% women) were recruited. Fat, muscle, bone parameters, basic demographics, medical history, physical performance and activity, and calcium intake of participants were obtained from datasets. The diagnosis of osteoporosis, sarcopenia, and obesity was based on current reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Additionally, this study had limitations in that it could not quantitatively measure the amount of exercise of the subjects. It is well known that sarcopenia prevention [ 50 ] and educational interventions [ 51 ] including exercise have beneficial effects on bone health. We are currently conducting another intervention study to find answers about the effects of diet and exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this study had limitations in that it could not quantitatively measure the amount of exercise of the subjects. It is well known that sarcopenia prevention [ 50 ] and educational interventions [ 51 ] including exercise have beneficial effects on bone health. We are currently conducting another intervention study to find answers about the effects of diet and exercise.…”
Section: Discussionmentioning
confidence: 99%
“…A 2.3-fold increased risk of falls is reported for sarcopenic elderlies compared to the non-sarcopenic elders [ 5 ]. In patients with a fragility fracture [ 6 , 7 ], sarcopenia has been reported to reach up to 95% in males and 64% in females [ 8 ]. Recent studies have also shown that sarcopenia treatments in the United Kingdom (UK) costs approximately Great Britain Pound (GBP) 2.5 billion annually [ 2 , 9 ].…”
Section: Introductionmentioning
confidence: 99%